Pengembangan Media Pembelajaran IPA Konsep Asam-Basa Menggunakan Glide untuk Kelas VII - Zahroh,; Islamian, Lutfia Rahma Iman (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2023)
Teachers need innovative media and accommodate information technology, so that they can accommodate new learning systems and are compatible with students. The purpose of this research is to develop science learning media with acid-base concepts to increase students' interest and motivation. This research is included in the design-research with a small-scale trial class. The participants involved in this study were seven students. The learning media application was developed using the Glide platform based on the ADDIE model and then tested on the participants. The data in this study were obtained from a questionnaire that measured the interest and motivation of students after using learning media. The results showed that the majority of students' interests and motivations were positive towards the developed media. The results of this small-scale trial indicate that the science learning media made with the Glide platform are good from the aspect of stimulating the interest and motivation of students in science learning. Keywords: e-learning, Glide, learning media